Potential Benefits of Probiotics, Prebiotics, and Synbiotics on the Intestinal Microbiota of the Elderly - Bedani, Raquel; Isay Saad, Susana Marta; Sivieri, Katia [UNESP] (Elsevier, 2016)
Although the scientific evidence has shown that the aging process may affect the composition and metabolic activity of human intestinal microbiota and its interaction with the immune system, this relationship still requires a better understanding. Probiotics, prebiotics, and synbiotics have shown the potential to alleviate common gastrointestinal problems in elderly people by modulating microbial activity and immune status. In spite of the promising results, more intervention trials with probiotics and/or prebiotics are needed to elucidate the mechanisms of action involved and to undoubtedly demonstrate their effectiveness in aged people. The aim of this chapter is to focus on the gut microbial changes associated with aging and the potential benefits of pro-, pre-, and synbiotics to modulate the intestinal microbiota and to contribute for the maintenance of the health and well-being in the elderly.
Keywords: Aging; Gut health; Gut microbiota; Modulation; Prebiotics; Probiotics; Synbiotics